Shiva in a dancing posture - Temples of India Project Team (Jio Institute, 2024)
One of the surasenakas (pediment made of chaitya dormer) features a sculpture capturing the divine dance of Shiva. From the rear, Shiva’s upper body twists towards the front, conveying dynamic movement and cosmic rhythm. Though some of his arms are now broken, remnants of divine attributes are visible, including a damaru (drum) symbolizing the rhythm of creation, and other sacred objects. One of his arms extends in the gajahasta gesture, resembling an elephant trunk. He has a jatamukuta (crown of matted hair), a moustache, and a beard, and he is surrounded by celestial gandharvas (celestial musicians). This sculpture captures the timeless essence of Shiva’s cosmic dance, embodying the eternal flow of creation, preservation, and destruction.